ENGLISH AS A NATIONAL LANGUAGE - Khaydarova Nigora; Axmadjonova Oydinoy (TADQIQOTLAR, 2025)
Abstract: This thesis explores the role of English as a national language and its impact on social, cultural, and educational development within multilingual societies. The study examines how English functions as a unifying linguistic tool, facilitating communication among diverse ethnic and linguistic groups. It also analyzes the advantages and challenges associated with adopting English as a national language, including issues of identity, language preservation, accessibility, and educational equity. By reviewing global examples and theoretical perspectives, the research highlights how English contributes to national integration, global competitiveness, and modernization. The findings suggest that while English can promote social cohesion and international participation, careful policy planning is required to balance its use with the protection of native languages and cultural heritage.